2022
DOI: 10.1038/s42003-022-04150-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-cadherin is causal to pathologic changes in chronic lung disease

Abstract: Epithelial cells line the lung mucosal surface and are the first line of defense against toxic exposures to environmental insults, and their integrity is critical to lung health. An early finding in the lung epithelium of patients with chronic obstructive pulmonary disease (COPD) is the loss of a key component of the adherens junction protein called E-cadherin. The cause of this decrease is not known and could be due to luminal insults or structural changes in the small airways. Irrespective, it is unknown whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…E-cadherin is a transmembrane glycoprotein which presents on the lateral surfaces of epithelial cells and functions as a cell adhesion [ 24 ]. Loss of E-cadherin is associated with lung diseases such as asthma and chronic obstructive pulmonary disease [ 25 ]. HIF-1α signaling pathway may play a key role in the development of ALI.…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin is a transmembrane glycoprotein which presents on the lateral surfaces of epithelial cells and functions as a cell adhesion [ 24 ]. Loss of E-cadherin is associated with lung diseases such as asthma and chronic obstructive pulmonary disease [ 25 ]. HIF-1α signaling pathway may play a key role in the development of ALI.…”
Section: Introductionmentioning
confidence: 99%
“…25 Diseased COPD epithelium demonstrates decreased apical junctional proteins (ZO-1 (TJP1), OCLN, E-cadherin) compared with normal bronchial epithelium. 15,26,27 Notably, when the apical-adherens junction protein, E-cadherin, is not expressed in the epidermis, the tight junction proteins ZO-1 (TJP1), occludin, and claudins are also not properly formed, leading to reduced epithelial resistance in bronchial epithelial cells. 28 IPF patients have also been shown to have reduced protein expression of E-cadherin leading to increased alveolar permeability and subsequent chronic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen penetrance through a dysfunctional epithelial barrier is a common pathologic phenotype driving other fibroinflammatory airway diseases such as IPF and COPD 25 . Diseased COPD epithelium demonstrates decreased apical junctional proteins (ZO‐1 (TJP1), OCLN, E‐cadherin) compared with normal bronchial epithelium 15,26,27 . Notably, when the apical‐adherens junction protein, E‐cadherin, is not expressed in the epidermis, the tight junction proteins ZO‐1 (TJP1), occludin, and claudins are also not properly formed, leading to reduced epithelial resistance in bronchial epithelial cells 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has demonstrated that primary bronchial epithelial cells derived from patients with COPD have a significant reduction in E-cadherin levels compared to age- and sex-matched normal cells (15, 16). Moreover, we have found that loss of E-cadherin can drive epithelial dysfunction and tissue remodeling (15) in mouse models. However, mechanisms of modulating E-cadherin in COPD are unknown.…”
Section: Introductionmentioning
confidence: 97%